The art of wandering : the writer as walker - Coverley, Merlin (Oldcastle Books, 2012)
A philosophical history of that strange but prolific hybrid-the writer as walkerFrom the peripatetic philosophers of Ancient Greece to the streets of 20th-century London, Paris, and New York, the figure of writer as walker has continued to evolve through the centuries, the philosopher and the Romantic giving way to the experimentalist and radical. From pilgrim to pedestrian, flâneur to stalker, the names may change, but the activity of walking remains constant, creating a literary tradition encompassing philosophy and poetry, the novel and the manifesto; a tradition which this.